G37(P) An element of competition can improve journal club engagement. (27th April 2015) - McKeever, S; Kinney, S; Lima, S; Newall, F
Abstract : Background: Journal clubs (JC) can increase critical appraisal skills and aid in promoting evidence based practice. 1 Often, after an initial flourish, a JCs popularity wanes. 2, 3 Innovative approaches to improving JC participation are required 2 but few have been described. In 2013, to increase nurse's engagement with a hospital-wide nursing JC, a competition format was convened. Aim: To obtain an understanding of a competition elements impact on paediatric nurses JC engagement. Method: Twelve departments, of a dedicated paediatric hospital, were randomly assigned a month to present JC. Departmental nurses were supported to evaluate an article according to a framework. 4 A predetermined rubric guided marking. Post competition, with ethics committee approval (HREC-33167), all hospital nurses received an anonymous online survey invitation. Demographic, Likert scale and freeform information was collected. Questions elicited attitudes and perceived barriers or facilitators to JC. Freeform data was themed. Survey completers could provide separate details to win a voucher. Results: Compared to the previous year there was a significant increase in JC attendance (2013 mean = 22 vs. 2012 mean=10, t-test p = 0.00001). Full online survey responses were received from 289/1674 (response rate 17.3%) of sent invitations (non-attendees n = 224, attendees n = 65 (18 presenters). Overall, attendees reported JC had a positive impact on their professional engagement, as shown in Figure 1 . Presenters rated highly the JC format as it developed skills and increased JC confidence, as shown in Figure 2 . Freeform themes indicated issues of time, session location, JC advertising and increased topic variety. Conclusion: A competition format can increase nurses JC engagement and participation. Further work is required to establish applicability of this format to other settings. References: Harris J, Kearley K, Heneghan C, et al . Are journal clubs effective in supporting evidence-based decision making? A systematic review. BEME Guide No. 16. Med Teacher 2011;33:9–23. Swift G. How to make journal clubs interesting. Adv Psychiatr Treat. 2004;10:67–72. Silversides A. Journal clubs: A forum for discussion and professional development. Can Nurse 2011;107:18–23. Schwartz MD, Dowell D, Aperi J, Kalet AL. Improving journal club presentations, or, I can present that paper in under 10 minutes. Evid Based Med. 2007;12:66–8.